Ferroptosis in lung cancer: dual role, multi-level regulation, and new therapeutic strategies - Li, Yunbin; Li, Xiaosong; Li, Jian (Frontiers in Oncology, 2024)
Lung cancer is a highly prevalent malignant tumor worldwide, with high incidence and death rates. Recently, there has been increasing recognition of the role of ferroptosis, a unique cell death mechanism, in lung cancer. This review aims to summarize the current research progress on the relationship between ferroptosis and lung cancer. It also provides a comprehensive analysis of the regulatory processes of ferroptosis in various stages, including epigenetics, transcription, post-transcription, translation, and posttranslation. Additionally, the review explores the dual nature of ferroptosis in lung cancer progression, which presents interesting therapeutic possibilities. On one hand, ferroptosis can promote the escape of immune surveillance and reduce the efficacy of treatment in the early stages of tumors. On the other hand, it can counter drug resistance, enhance radiosensitivity, and promote immunotherapy. The article also discusses various combination treatment strategies based on the mechanism of ferroptosis.Overall, this review offers a holistic perspective on the role of ferroptosis in the onset, progression, and treatment of lung cancer. It aims to contribute to future research and clinical interventions in this field.treatments,